1987
DOI: 10.2527/jas1987.6561639x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hay Substitution on Intake and Digestibility of Forage Rape (Brassica napus) Fed to Lambs2

Abstract: Intake and digestibility trials were conducted with sheep to evaluate the effect of adding various levels of a typical fibrous grass forage (neutral detergent fiber, NDF = 68%) to a high quality, low fiber (NDF = 22%) brassica forage. Four forage rape:orchardgrass hay diets (0, 40, 70, 100% rape content on a dry matter basis) were fed to groups of six Polled-Dorset crossbred growing wether lambs (39.6 kg) individually housed in metabolism crates. After a 7-d ad libitum intake period, a 7-d digestibility trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…Lambert et al (1987) observed that lambs offered 100% rape relative to a 70% rape diet had reduced DMI by 15%, suggesting that the low DM concentration of brassica (i.e. kale, rape) forages reduced DMI via the gut fill effect of intracellular water.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Lambert et al (1987) observed that lambs offered 100% rape relative to a 70% rape diet had reduced DMI by 15%, suggesting that the low DM concentration of brassica (i.e. kale, rape) forages reduced DMI via the gut fill effect of intracellular water.…”
Section: Discussionmentioning
confidence: 91%
“…However, the greater buffering properties of kale compared to grass silage probably contributed to the absence of a depression in ruminal pH as dietary grass silage proportion decreased. Brassicas contain about 80-95% water (Lambert et al, 1987); the high bulk density of forage kale has been shown to increase mastication in cows (Gazzola et al, 2007) thus increasing saliva production and consequently buffering rumen pH which probably contributed to the absence of a larger decline in rumen pH on diet K100.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the ability of forage rape and stubble turnips, irrespective of nitrogen level and sowing date, to maintain CP concentrations over the growing season allows considerable flexibility to the producer when utilizing the forage crops with animals. Furthermore, in vitro digestibilities are consistently high among forage brassica crops and may exceed 900 g kg −1 (Lambert et al. , 1987; Armstrong et al.…”
Section: Discussionmentioning
confidence: 99%
“…The high water content of brassica forage may physically limit feed consumption (Lambert et al, 1987;GuiUard et al, 1988). Low-fiber brassica forage is similar in composition to a high-moisture concentrate feed (Guillard and Allinson, 1988) and may be unsuitable as the sole diet for ruminants (Lambert et al, 1987;Cassida, 1992). Provision of hay to animals grazing brassica pastures addresses these concerns by diluting antiquality compounds and increasing dry matter (DM) and fiber content of diets.…”
Section: Introductionmentioning
confidence: 99%